Reconstruction of the Role of the Financial Services Authority in Overcoming Fraud in the Business Sector in Indonesia - Suhardi Suhardi; Bambang Bernanthos (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The objective of this study is to investigate how the Financial Services Authority (OJK) is actively tackling fraud within the Indonesian business community. Fraud is a criminal act that poses a significant threat to corporate finances and undermines public confidence, ultimately jeopardizing the credibility of financial markets. Therefore, this research focuses on analyzing the role of the OJK in detecting, preventing, and overcoming fraudulent practices in the business environment. The research results indicate that the OJK's role should be reconstructed by increasing inter-agency cooperation, strengthening regulations, and implementing innovative financial technology. This research highlights the importance of enhancing OJK's capacity in several key areas such as fraud detection, employee training, and promoting awareness among stakeholders. It is essential to increase transparency, accountability, and active involvement of the private sector to mitigate the risk of fraud.